2018
DOI: 10.1161/jaha.117.008160
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Associations of Global Electrical Heterogeneity ECG Phenotype: The ARIC (Atherosclerosis Risk in Communities) Study and CHS (Cardiovascular Health Study)

Abstract: Background ECG global electrical heterogeneity (GEH) is associated with sudden cardiac death. We hypothesized that a genome‐wide association study would identify genetic loci related to GEH.Methods and ResultsWe tested genotyped and imputed variants in black (N=3057) and white (N=10 769) participants in the ARIC (Atherosclerosis Risk in Communities) study and CHS (Cardiovascular Health Study). GEH (QRS‐T angle, sum absolute QRST integral, spatial ventricular gradient magnitude, elevation, azimuth) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…The insulin‐like growth factor 1 ( IGF1 ) signaling pathway regulates exercise‐induced physiological cardiac hypertrophy and cardiac protection (Weeks et al, ). Tereshchenko et al recently identified a GEH‐associated genetic polymorphism in the intron of the IGF1 ‐receptor ( IGF1R ) gene (Tereshchenko et al, ). As demonstrated by an IGF1R locus‐associated GEH phenotype (Figure e in (Tereshchenko et al, )), physiological cardiac remodeling in the athlete's heart is characterized by sizable increase in SAI QRST and SVG magnitude with only mild increase in SVG azimuth and QRS‐T angle and simultaneous decrease in SVG elevation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insulin‐like growth factor 1 ( IGF1 ) signaling pathway regulates exercise‐induced physiological cardiac hypertrophy and cardiac protection (Weeks et al, ). Tereshchenko et al recently identified a GEH‐associated genetic polymorphism in the intron of the IGF1 ‐receptor ( IGF1R ) gene (Tereshchenko et al, ). As demonstrated by an IGF1R locus‐associated GEH phenotype (Figure e in (Tereshchenko et al, )), physiological cardiac remodeling in the athlete's heart is characterized by sizable increase in SAI QRST and SVG magnitude with only mild increase in SVG azimuth and QRS‐T angle and simultaneous decrease in SVG elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Tereshchenko et al recently identified a GEH‐associated genetic polymorphism in the intron of the IGF1 ‐receptor ( IGF1R ) gene (Tereshchenko et al, ). As demonstrated by an IGF1R locus‐associated GEH phenotype (Figure e in (Tereshchenko et al, )), physiological cardiac remodeling in the athlete's heart is characterized by sizable increase in SAI QRST and SVG magnitude with only mild increase in SVG azimuth and QRS‐T angle and simultaneous decrease in SVG elevation. Thus, GEH presentation can potentially distinguish athletes with physiological RV remodeling from those who are overtrained and are at risk to develop RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…26 Early cardiac development affects the generation of electrophysiological heterogeneities in the adult heart. 27 There may be a genetic basis for this phenomenon as GEH-associated genetic polymorphisms indicated the involvement of HAND1 and TBX3 genes, 4 both of which play a role in outflow tract development.…”
Section: Triggers or Transient Substrate Of Scd Eventmentioning
confidence: 99%
“…Many GEH-associated genetic loci are implicated in cardiac development. 4 Further studies of the underlying biology behind GEH-associated loci will help to uncover novel mechanisms of SCD and develop primary prevention strategies. A recent case-control genomewide association study (GWAS) of sudden cardiac arrest 32 did not identify any variants at genome-wide statistical significance.…”
Section: Intermediate and Long-term Substrates Of Scdmentioning
confidence: 99%
See 1 more Smart Citation